Study of 2-aminoquinolin-4(1H)-one under Mannich and retro-Mannich reaction - Funk, Petr; Motyka, Kamil; Soural, Miroslav; Malon, Michal; Koshino, Hiroyuki; Kusz, Joachim; Hlavac, Jan (PLOS ONE, 2017)
2-Aminoquinolin-4(1H)-one was reacted with various primary/secondary amines and paraformaldehyde under Mannich reaction conditions. In the case of secondary amines, the reaction in N,N-dimethylformamide yielded expected Mannich products accompanied with 3,3'-methylenebis(2-aminoquinolin-4(1H)-one). Except these main products, the pyrimido[4,5-b]quinolin-5-one derivative was also identified as co-product. The reaction with primary amines led to the formation of pyrimido[4,5-b]quinolin-5-ones. The Mannich reaction products were thermally unstable and afforded a mixture of bis-(2-aminoquinolin-4(1H)-one) and tris-(2-aminoquinolin-4(1H)-one) derivative, probably via reactive methylene species. This retro-Mannich reaction was tested in reaction with indole and thiophenole as nucleophilles, and appropriate conjugates were formed. The mechanism of above discussed reactions in which 2-aminoquinolinone displays the nucleophilicity on C3 carbon as well as N2 nitrogen is discussed.